The effect of the T6 heat treatment on the surface structure and oxide layer of an Al-Si coat - Kucharska, Barbara; Wróbel, Anna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The paper presents investigation results for an Al-Si protective coat deposited from a liquid phase on the ferritic steel surface. A coat of chemical composition of Al - 6.5 wt.% Si was subjected to a T6 heat treatment at temperatures of 420 °C (solutionizing), and 80 °C and 120 °C (ageing). The effect of soaking on the structure of the Al-Si coat was determined by microscopic examination. By XRD examination, the effect of soaking on the phase composition of the coat, while by GXRD examination, the oxide layer composition were determined. It was found that relaxation of the coat surface layer (a decay of the technological cold work effects) occurred, and a highly dispersed oxide layer Al2SiO5 formed as a result of the heat treatment.
Optica Applicata, Vol. 39, 2009, nr 4, s. 889-896
Keywords: optyka; Al-Si coatings; T6 treatment; oxides Al2O3/SiO2; XRD/GXRD measurements